2010
DOI: 10.1016/j.yexmp.2010.03.008
|View full text |Cite
|
Sign up to set email alerts
|

α1-Acid glycoprotein production in rat dorsal air pouch in response to inflammatory stimuli, dexamethasone and honey bee venom

Abstract: This study shows the rapid and differential production of the 40–43 kDa and the 70–90 kDa α1-acid glycoprotein (AGP) fucosylated glycoforms after treatment of the dorsal air pouch with bacterial lipopolysaccharide (LPS), HgCl2 or Freund's complete adjuvant (FCA). The 40–43 kDa and the 70–90 kDa AGP production is peaked 1–3 h post-LPS treatment. We observed that the responses to LPS and FCA are similar in that both AGP isoforms are induced whereas they differ in that the FCA exhibits a 6 h lag period. The respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 42 publications
0
2
0
9
Order By: Relevance
“…Our results exhibited an increase in pro-inflammatory cytokines secretion (TNF-α, IL-6, IFN-γ) in infected non-treated mice compared to control ones, indicating the inflammatory responses attributed to Cryptosporidium infestation. Earlier investigations found that α1-globulin is significantly elevated in rats infected with C. parvum [ 53 ] through an increasing level of serum amyloid A and/or serum amyloid P that were previously confirmed to be increased during infection [ 62 ] and inflammation [ 63 ]. Interestingly, a landmark study has revealed a significant increase in the expression of TNF-α, IL-6 genes in leukocytes of C. parvum -infected mice [ 64 ].…”
Section: Discussionmentioning
confidence: 94%
“…Our results exhibited an increase in pro-inflammatory cytokines secretion (TNF-α, IL-6, IFN-γ) in infected non-treated mice compared to control ones, indicating the inflammatory responses attributed to Cryptosporidium infestation. Earlier investigations found that α1-globulin is significantly elevated in rats infected with C. parvum [ 53 ] through an increasing level of serum amyloid A and/or serum amyloid P that were previously confirmed to be increased during infection [ 62 ] and inflammation [ 63 ]. Interestingly, a landmark study has revealed a significant increase in the expression of TNF-α, IL-6 genes in leukocytes of C. parvum -infected mice [ 64 ].…”
Section: Discussionmentioning
confidence: 94%
“…BV has been used as a traditional medicine to treat chronic inflammatory (arthritis, rheumatism and back pain) (Chang and Bliven, 1979;Kwon et al, 2001;Kim et al, 2003;Son et al, 2007;Park et al, 2008;Vasileiadou et al, 2010) and skin (Escrig et al, 1997;Han et al, 2012) diseases. In fact, the anti-inflammatory properties of BV samples from different origins such as Egypt (Amin and Abdel-Raheem, 2014), Korea (Park et al, 2007;Park et al, 2008;Lee et al, 2009), USA (Chang and Bliven, 1979) and even commercial samples (Jang et al, 2005;Moon et al, 2007;Yoon et al, 2008) have been reported in apitherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, αναστέλλει την ενεργοποίηση των πολυμορφοπύρηνων ουδετερόφιλων κυττάρων (Vasson et al, 1994), τροποποιεί την επαγόμενη από LPS έκκριση κυτοκινών από μονοκύτταρα/μακροφάγα (Boutten et al, 1992) και αυξάνει την έκκριση του αναστολέα της IL-1 από τα μακροφάγα μυός, κυρίως του ανταγωνιστή του υποδοχέα της IL-1 (IL-1Ra) (Bories et al, 1990;Tilg et al, 1993). Επίσης, δρα συνεργιστικά με τον LPS και αυξάνει την έκκριση της IL-6 από τα μονοπύρηνα κύτταρα του αεροθύλακα επίμυων (Vasileiadou et al, 2010). In vivo, αποτρέπει την απόπτωση που επάγεται από τον TNFα σε κύτταρα ποντικού (Libert et al, 1994 (Crestani et al, 1998).…”
Section: βιολογικός ρόλοςunclassified
“…Παράλληλα, οδηγεί σε μείωση των επιπέδων της AGP στον ορό και την αύξησή της τοπικά στην άρθρωση στα αρχικά στάδια ανάπτυξης της νόσου (Vasileiadou et al, 2010). Το γεγονός αυτό δείχνει την πιθανή διαφορική δράση της AGP που εξαρτάται από την τοπική (άρθρωση) ή τη γενικευμένη (ορός) παραγωγή της στα αρχικά στάδια της νόσου.…”
Section: πρωτεΐνες οξείας φάσης και πειραματικά μοντέλα αρθρίτιδαςunclassified
See 1 more Smart Citation